FAKTOR-FAKTOR YANG MEMPENGARUHI KELELAHAN MATA (ASTENOPIA) PADA PENGGUNA KOMPUTER DI JAMBI EKSPRESS TAHUN 2022 - Nur Hidayatun Nikmah; Eko Mirsiyanto; Eti Kurniawati (Jurnal Inovasi Penelitian, 2023)
Eye fatigue (asthenopia) is a symptom that occurs due to excessive computer use without resting the eyes or in an unergonomic position, viewing distances on monitors that are too close and lack of lighting in the workplace. Such conditions can reduce occupational health and can even cause work accidents. Therefore, this study was conducted to determine the factors that affect eye fatigue (asthenopia) in computer users at Jambi Ekspress in 2022. This study was conducted using a quantitative method with a Cross Sectional approach. The research sample was 35 people using the total sampling technique, namely all workers who use computers in Jambi Ekspress. This research was conducted on 16-28 May 2022. The data analysis used was Univariate and Bivariate Analysis with Chi Square Test. The results of the analysis show that there is a significant relationship between viewing distance on the monitor (p-value = 0.032) and lighting intensity (p-value = 0.049) with eye fatigue (asthenopia) on computer users in Jambi Ekspress in 2022. There is no significant relationship. between eye rest (p-value = 0.078) and duration of computer use (p-value = 0.067) and eye fatigue (asthenopia) on computer users in Jambi Ekspress in 2022. It is recommended for Jambi Ekspress to conduct regular eye health checks on workers , conduct "fun day" to overcome work stress and regulate the intensity of lighting in the workplace. For workers to relax their eyes every hour of computer use, work ergonomically and work with a monitor distance of > 50 cm so as to prevent eye fatigue (asthenopia).